Impacts of IOD and ENSO on the phytoplankton’s vertical variability in the Northern Indian Ocean - Qiwei Hu; Xiaoyan Chen; Xianqiang He; Yan Bai; Tingchen Jiang; Yu Huan; Zhanlin Liang (Frontiers in Marine Science, 2025)
The Indian Ocean Dipole (IOD) and El Niño–Southern Oscillation (ENSO) are the primary climatic modes that profoundly impact physical and biological processes in the Northern Indian Ocean (NIO). IOD- and ENSO-related vertical phytoplankton anomalies, however, remain poorly understood. Using the three-dimensional Chlorophyll a concentration dataset generated by a machine learning model, this study examines IOD- and ENSO-linked vertical phytoplankton anomalies over the entire euphotic layer (0–100 m) in the NIO during 2000–2019. Results reveal that IOD and ENSO trigger significant opposite changes in phytoplankton at 0–50 m and 50–100 m. The effects of IOD and ENSO on the vertical structure of phytoplankton are generally asymmetric, with anomalies at 0–50 m being significantly larger than that at 50–100 m. During summer and fall, the significant vertical phytoplankton anomalies in the Central Arabian Sea (CAS), Southern Tip of India (STI), and the Eastern Equatorial Indian Ocean (EEIO), are primarily related to IOD forcing. IOD-linked negative (positive) phytoplankton anomalies at 0–50 m (50–100 m) are driven by the westward propagating downwelling Rossby waves. During winter and spring, due to the local wind anomalies and shallower thermocline, the Seychelles–Chagos Thermocline Ridge (SCTR) is the only region where ENSO exhibits greater positive effects on phytoplankton at 50–100 m than IOD. Different from IOD, the ENSO-related wind reversal impedes subsurface upwelling in the STI and EEIO, thereby constraining vertical biological activity. These findings could shed light on how phytoplankton will respond to changing ocean dynamics under global warming.